2017
DOI: 10.1016/j.aja.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the video laryngoscopes with Macintosh laryngoscope for nasotracheal intubation

Abstract: As compared with the Macintosh laryngoscope, the GlideScope video laryngoscope facilitated nasotracheal intubations with shortened intubation time and reduced intubation difficulty in patients undergoing oromaxillofacial surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 17 publications
3
32
0
Order By: Relevance
“…Numerous studies have shown that the use of a videolaryngoscope diminishes the necessity of these additional maneuvers, which may result in shorter NTI times as compared to the use of a direct laryngoscope. Tseung et al [28]. reported that use of the GlideScope or Pentax AWS leads to reduced application of BURP, and Hazarika et al [29].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that the use of a videolaryngoscope diminishes the necessity of these additional maneuvers, which may result in shorter NTI times as compared to the use of a direct laryngoscope. Tseung et al [28]. reported that use of the GlideScope or Pentax AWS leads to reduced application of BURP, and Hazarika et al [29].…”
Section: Discussionmentioning
confidence: 99%
“…It is much bigger than the blade of traditional DL or MVL. 24 The bulky blade of PVL can make it difficult to insert a PVL into the mouth, which might increase the TTI. In a previous study comparing MVL and PVL during orotracheal intubation, although PVL provided superior glottic view over MVL, the TTI and ease of intubation were similar between the two devices.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that our main finding -higher variability in driving pressures and tidal volumes with pressure-compared with volume-controlled ventilation, should be independent of the airway device used. Perhaps pressure control ventilation may be more effective at achieving sufficiently high tidal volumes in case of a substantial air-leak, although newer supraglottic airways devices may have fewer issues with air leaks [2].…”
Section: Mechanical Ventilation Mode and Postoperative Pulmonary Compmentioning
confidence: 99%
“…Obviously, a size-4 GlideScope blade would not be suitable for the paediatric patients included in this study. The design of the blade can affect the performance of videolaryngoscopy for nasotracheal intubation [2], in particular, acute distal angulation and the large size of the GlideScope blade, which can complicate use of the straight Magill forceps, in comparison with the Macintosh blade of the C-MAC videolaryngoscope; Boedeker curved forceps are recommended instead when an angulated-typed videolaryngoscope is used for nasotracheal intubation [3]. In addition, could the authors state which type of GlideScope videolaryngoscope was used in this study -Original, Cobalt, Ranger or Titanium -as different GlideScope videolaryngoscopes can have an effect [4]?…”
Section: Mechanical Ventilation Mode and Postoperative Pulmonary Compmentioning
confidence: 99%